2011
DOI: 10.1186/bcr2995
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultrasound elasticity imaging to monitor the response of a primary breast cancer to neoadjuvant chemotherapy in one patient in a pilot study

Abstract: IntroductionThe automated breast volume scanner (ABVS) is the fi rst of its kind and utilises a large, 17 cm × 15 cm high-frequency ultrasound probe which sweeps across the whole breast generating images that can be reformatted into multiple planes and a 3D volume. ABVS will change breast ultrasound practice by: introducing operator standardisation, reproducibility and repeatability of measurement and interpretation; changing who acquires the volume set and how breast ultrasounds are reported; and allowing acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Elastography and shear wave ultrasound imaging have been used in clinical trials for the differentiation of benign and malignant breast tumors with considerable success (Tanter et al 2008, Evans et al 2010, Sebag et al 2010. Experiments are now underway to measure the changes in shear wave propagation as a function of treatment, while evidence that elastography can detect such changes have been reported (Bando et al 2007, Brindle 2008, English et al 2011, Hayashi et al 2012. Future work will include detailed studies of the longitudinal response of individually treated cells in a more controlled environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elastography and shear wave ultrasound imaging have been used in clinical trials for the differentiation of benign and malignant breast tumors with considerable success (Tanter et al 2008, Evans et al 2010, Sebag et al 2010. Experiments are now underway to measure the changes in shear wave propagation as a function of treatment, while evidence that elastography can detect such changes have been reported (Bando et al 2007, Brindle 2008, English et al 2011, Hayashi et al 2012. Future work will include detailed studies of the longitudinal response of individually treated cells in a more controlled environment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that these modalities can be used for the detection of tumors based on quantitative stiffness measurements (Findings et al 2012, Berg et al 2012. A number of recent studies have led us to hypothesize that both ultrasound compression and shear wave elastography imaging could also be used for cancer treatment monitoring (Bando et al 2007, Brindle 2008, English et al 2011, Hayashi et al 2012. Similarly, magnetic resonance (MR) elastography has been shown to have potential in similar clinical applications.…”
Section: Introductionmentioning
confidence: 99%